THE PRINCIPLES OF CONTRACTUAL FREEDOM AND GOOD FAITH IN JURIDICAL CONTRACTS - MIHAELA IRINA IONESCU (Challenges of the Knowledge Society)
The contract is the very heart of the Civil Code, and it is in fact also the cornerstone of any society, as without it relations and rapport amongst citizens could not occur nor unfold, and as such it is presently considered an effective legal instrument for organizing the behavior of all members of society. The importance of contracts, the extent of contractual freedoms, the rapports that contracts entertain with laws, norms and other regulations and the means to properly frame and limit the State’s intervention in the economy all hinge on the evolution of society and it’s general ideological proclivity. The contract acts as the mirror of all this and it comes as no surprise that a society that has shortly left an organization based on the tenants of communism still bears the full weight of this ideology when it comes to contracts. In the framework of the New Civil Code, the contract is viewed as based on a series of principles which are carefully drawn and well established in the general consciousness. As such, altering these principles would naturally cause important concern and uncertainty between the Parties to the Contract. Therefore, when times require repealing from a principle, this should be implemented with the greatest prudence by the legislature. This paper contains a summary of the guiding principles of contracts from the provisions of the New Civil Code. For the first time in our legal history, these provisions regulate the two most fundamental principles of contracts; contractual freedom and good faith, which is why the author chose to insist on these new regulations